Indocyanin greens cholangiography for intra-operative bile duct visualization during pediatric laparoscopic hepato-biliary surgery - Jarruphong Noitumyae (Elsevier, 2021)
Introduction: Intraoperative cholangiography involving the excretion of fluorescent indocyanine green (NIR/ICG) into the bile is used to determine biliary anatomy in adult laparoscopic cholecystectomy (LC) and other hepatobiliary surgery. Objectives: This study aimed to evaluate the features of intraoperative ICG cholangiography in 3 cases The 1st case of pediatric LC with previous cholelithiasis & Cholecystitis, and The 2nd and 3rd cases of choledochal cyst with previous pancreatitis then compare the delineation of the hepatic duct (HD), cystic duct (CD), common bile duct (CBD) between ICG cholangiography, magnetic resonance cholangiopancreatography (MRCP) and intraoperative finding. The ICG 0.2 mg/kg was injected intravenously before operation 2 hours to demonstration. Result: We performed 3 cases of pediatric laparoscopic hepato-biliary surgery under NIR/ICG visualization. No conversions to open occurred. No adverse and allergic reactions to NIR/ICG or other postoperative complications were reported. Conclusion: Indocyanin Green cholangiography for intraoperative bile duct visualization during laparoscopic surgery enables a better identification of the biliary tree and thus increases surgical safety.